Resposta :
[tex]\large\boxed{\begin{array}{l}\sf Deve-se\,isolar\,os\,elementos\\\sf desconhecidos\,em\,um\,dos\,lados\,do\,sinal\,de\\\sf igual\,e\,os\,valores \,constantes\,do\,outro\,lado.\end{array}}[/tex]
[tex]\large\boxed{\begin{array}{l}\sf Quando\, um \,termo \,da \,equac_{\!\!,}\tilde{a}o\, mudar \,de \\\sf lado \,do \,sinal \,de\, igual, devemos \,inverter\, a \\\sf operac_{\!\!,}\tilde{a}o.\, Assim, se \,tiver \,multiplicando, \\\sf passar\acute{a}\, dividindo, se\, tiver \,somando, \\\sf passar\acute{a} \,subtraindo\, e\, vice-versa.\end{array}}[/tex]
[tex]\large\boxed{\begin{array}{l}\underline{\bf Soluc_{\!\!,}\tilde ao}\\\sf4x+2+36=10\\\sf4x+38=10\\\sf4x=10-38\\\sf 4x=-28\\\sf x=-\dfrac{28}{4}\\\Huge\boxed{\boxed{\boxed{\boxed{\sf x=-7}}}}\end{array}}[/tex]
Resposta: -7
Explicação passo a passo:
4x+2+36=10
4x=10-2-36
4x=-28
x=-28/4
x=-7